Root colonization of oil palm (Elaeis guineensis Jacq.) Using GFP-Expressing Ganoderma boninense and effects of lignin on disease progression - Thopla Govender, Nisha (2016)
Oil palm is the world’s most efficient oil-bearing tree. Major diseases impeding the oil palm productivity have been caused by fungi, particularly Ganoderma boninense, the causal agent of basal stem rot (BSR). Visible symptoms can only be observed nearing the plant death stage while early penetration and infection strategy remain cryptic due to the fungal hyaline nature. The underlying principles on how Ganoderma penetrates and infects oil palm roots are unknown. Therefore, a tagged G. boninense harbouring GUS-GFP fusion gene would ideally serve as a tool to unravel early pathogenesis of G. boninense. Lignin, a heterogeneous complex polymer is poorly understood during BSR development and thus, assessments of lignin content and composition in different planting materials and during the disease development were performed. In addition, enzyme activity and gene expression of key components in the phenylpropanoid pathway were investigated. Lignin content and composition were screened in oil palm lines with differential tolerance to BSR. Both parameters were associated to growth factors (height, weight and girth) and micronutrients depositions were measured using X-Ray Fluorescence (XRF). Efficient Agrobacterium-mediated transformation protocol was established via optimization of several parameters; Agrobacterium strain (LBA4404, GV3101, EHA101 and EHA105), explants (mycelia, spore and protoplast), vir gene induction period and modification of binary vector. The transformant was utilized to discern early stage colonization of BSR using the confocal microscopy. Glass-house trial on BSR development was performed to evaluate enzyme activities and gene expression of the following defence genes; phenylalanine ammonia lyase (PAL), cinnamyl alcohol dehydrogenase (CAD) and peroxidase (POD) using enzyme assay and quantitative real-time PCR respectively. Lignin content and composition were significantly different among the oil palm seedlings with different tolerance to BSR. The susceptible and intermediate lines showed significantly higher lignin content in comparison to the tolerant line, while lignin composition denoted as S/G ratio was higher in tolerant line in comparison to both susceptible and intermediate lines. Apparent lignin accumulation was supported by micronutrients deposition which comprised copper, silicon, titanium and sulphur. A successful transformation system was developed for G. boninense using protoplast and Agrobacterium strain LBA 4404. The binary vector pCAMBIA 1304, modified to harbour GPD fungal promoter from plasmid p416 improved the expression of GUS-GFP fusion protein. Colonization pattern was initiated with active differentiation of the tagged G. boninense into microhyphae. The needle-like structure was able to penetrate the epidermis layer randomly and progressed longitudinally into exodermis and cortex region. Induced lignification during defense showed great participation from both PAL and CAD genes and enzymes. The S/G ratio increased significantly in the induced lignin as compared to constitutive lignin indicated alterations employed by host as part of their defense strategy during Ganoderma infection. Low lignin content supported growth without compromising oil palm biomass while creating an avenue for greater proportion of induced lignin which consists of S monomer during G. boninense infection. The findings can be adopted in oil palm breeding strategies aimed to produce resistant planting materials.